2010
DOI: 10.1007/s10661-010-1482-8
|View full text |Cite
|
Sign up to set email alerts
|

Empirical assessment of incorporating sediment quality triad data into a single index to distinguish dominant stressors between sites

Abstract: Benthic infaunal community structure, sediment contamination, and sediment toxicity data (Sediment Quality Triad) were condensed into a single index based on the area of tri-axial plots, which were examined in relation to various habitat parameters. The purpose was to assess its utility for evaluating the relative impact of contaminants versus other stressors on benthic communities. The regression relationship between the areal index and the Effects Range-Median quotient (ERMq) was used to separate contaminant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Main contributors to the contamination of lake ecosystems are runoff from agricultural activities and industrial and municipal effluents [ 1 , 2 ]. Sediments are important components of the aquatic environment and constitute a particular concern from an environmental toxicology perspective, as they can retain persistent and toxic chemicals at levels many times greater than concentrations typically found in the water column [ 3 ]. Contaminated sediments may pose direct threats to benthic biota and to organisms that feed on the benthos [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Main contributors to the contamination of lake ecosystems are runoff from agricultural activities and industrial and municipal effluents [ 1 , 2 ]. Sediments are important components of the aquatic environment and constitute a particular concern from an environmental toxicology perspective, as they can retain persistent and toxic chemicals at levels many times greater than concentrations typically found in the water column [ 3 ]. Contaminated sediments may pose direct threats to benthic biota and to organisms that feed on the benthos [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…synthetic organic chemicals, polycyclic aromatic hydrocarbons (PAHs), trace metals, pharmaceuticals, etc.) from industrial, agricultural, urban and maritime activities can accumulate in this matrix and reach concentrations frequently higher than those detected in the water column (Hartwell et al 2010;den Besten et al 2003). In the sediment-water interface, these compounds may be resuspended, transported and redeposited far from their original source, producing negative effects to the benthic biota and biomagnification events along the food chain, with possible concern to the human health (Cesar et al 2007;Hartwell et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(2011b) found that three different kinds of sediment quality guidelines(PECs, ERMs, and LRMs) that are based on national data sets underestimated sediment toxicity when compared to the results of sitespecific toxicity testing using amphipods. The most reliable predictor of sediment toxicity was found to be the mean PEC-Q model based on site-specific results for the Calcasieu Estuary Hartwell et al (2011). described an innovative approach to sediment assessments that involves condensing the results of the Sediment Quality Triad into a single numerical index based on the area of tri-axial plots of relative contamination, toxicity, and benthic species richness.The relationship between this index and other measures of stressor effects may be a useful tool for discrimination between sites where chemical stressors predominate or where other environmental factors contribute to degraded sediment conditions.…”
mentioning
confidence: 99%